Understanding Risk Attitudes in two Dimensions: An Experimental Analysis - Jianying Qiu; Eva-Maria Steiger (University of Innsbruck, Department of Public Finance, 2009)
Despite extensive studies, the nature of risk attitudes remains a vigorously discussed question in economics and psychology. In expected utility theory, attitudes towards risk originate from changes in marginal utility. Cumulative prospect theory (CPT) adds an additional dimension: the weighting of probabilities. By examining both dimensions, we strive to gain more insight on the relation between the curvature of utility function and probability weighting, and on possible relations to cognitive limitations. Our findings from a controlled laboratory experiment suggest that the two dimensions capture quite different characteristics. Though, most individuals exhibit concave utility and convex probability weighting, the two dimensions show no significant correlation. In addition, only probability weighting, not the curvature of utility function, is correlated with educational background and decision time, which suggests its relation to cognitive limitations.
Keywords: C91; D81; 330; Risk attitudes; cumulative prospect theory; experimental study; Risikopräferenz; Prospect Theory; Erwartungsnutzen; Test